A comparative analysis of Slovenian and selected foreign syllabi for geography at the general secondary level of education - Konečnik Kotnik, Eva (Journal for Geography, 2008)
This contribution presents the results of a comparative analysis of Slovenian syllabi of 1998 and 2008 for geography in general secondary school and selected foreign syllabi for geography at the general secondary level of education. The structure of syllabi, the representation of learning objectives in relation to the global orientation (geographical knowledge, geographical and cross-curricular skills and abilities, upbringing), as well as the vertical selection and arrangement of geographical learning content were the criteria for this comparative analysis. There are differences in all the criteria among various syllabi, but in the case of Slovenian syllabi shifts in the direction of greater comparability with the English syllabus can be perceived.